Implementasi pembentukan karakter siswa melalui budaya sekolah di MTs Almaarif 02 Singosari - syidad, ahmad wildan (Maliki Interdisciplinary Journal, 2024)
As time goes by, character education in Indonesia has become increasingly minimal in terms of its implementation. In fact, what we know is that character education is very important to form humans who humanize humans. By familiarizing myself with the school culture at MTs Almaarif 02 Singosari, it is hoped that it will be able to form students who have characters that are in accordance with Aswaja teachings. This research uses descriptive qualitative research methods by carrying out 3 stages (1) observation, (2) interviews, and (3) documentation. The results of this research show that the implementation of character-building through school culture is indeed very effective. MTs Almaarif 02 Singosari is an example of a school that applies religious school culture in forming the character of its students. Starting from when students arrive, they check their headgear and hair, carry out congregational Dhuha prayers, perform al-Qur’an tadarus, read prayers before studying, BTQ coaching, and sanctions for violators which must not be violent. The obstacle experienced during implementing the school culture series is the lack of student awareness. Many students underestimate the rules made by the school because the existing sanctions do not involve violence. Students also feel that wearing a kopyah to school is old-fashioned. Therefore, teachers need direction and guidance to provide an understanding of the importance of school culture in shaping students’ character for the better.